Brand Discourse Analysis (BDA): Conceptual and Methodological Propositions - Wijaya, Bambang Sukma (Jobmark: Journal of Branding and Marketing Communication, 2020)
Brand Discourse Analysis (BDA) is a theory and method for analyzing how discourse is represented, reproduced, and circulated through messages, initiatives, or programmatic endeavors, means of communication, and conditions or ecosystems in which brands grow and develop. Several dimensions or aspects of BDA are: 1) Brand Message, which includes three elements, namely: Promo, Promise, and Prominence, 2) Brand Mode includes Strategy, Style, and Story, 3) Brand Medium consists of Channel, Chain, and Clique, and 4) Brand Milieu comprises Climate, Context, and Culture. In an increasingly hypermediated world, BDA has strategic implications in optimizing brand communication performance through various elements of discourse. Also, BDA has theoretical implications in enriching discourse analysis literature in the context of branding and marketing communications.